Occurrence and sources of resistance of sterility mosaic of pigeonpea - and Y.P.S. RATHI, A.K. SINGH, K.C. AGRAWAL (Indian Phytopathology, 2002)
The occurrence of sterility mosaic of pigeonpea [pigeonpea sterility mosaic virus, PSMV] in Chhattisgarh, India, is reported. Eriophyid mite vectors were observed on infected plants and inoculation of healthy plants resulted in symptoms of PSMV. Resistance against PSMV was evaluated by inoculating pigeonpea varieties using Aceria cajani. Of the 81 varieties tested, 10 were resistant, 7 were moderately resistant, 12 were susceptible and 53 were highly susceptible.